1996
DOI: 10.1175/1520-0477(1996)077<0473:saaowf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Salaries and Advancement of Women Faculty in Atmospheric Science: Some Reasons for Concern

Abstract: Zevin and Seitter's analyses of the 1993 American Meteorological Society membership survey indicated that university/college employees had the largest difference in salary by gender when controlling for experience and age. Further analyses of the membership survey presented here indicate that a large salary discrepancy exists for female full professors in atmospheric science. In addition, the small number of women at the associate professor rank suggests a "leaky pipeline" for female atmospheric science facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Disturbingly, salary differentials by gender within academe may be considerably larger than those outside of academe. For at least one discipline (atmospheric science), the salaries of PhD scientists holding senior level positions in private industry, federal research laboratories, and government positions were equitable by gender, whereas the average salaries of women full professors were substantially ($18,000) less than those of male faculty (Winkler et al 1996).…”
Section: An Uncomfortable Topicmentioning
confidence: 99%
See 2 more Smart Citations
“…Disturbingly, salary differentials by gender within academe may be considerably larger than those outside of academe. For at least one discipline (atmospheric science), the salaries of PhD scientists holding senior level positions in private industry, federal research laboratories, and government positions were equitable by gender, whereas the average salaries of women full professors were substantially ($18,000) less than those of male faculty (Winkler et al 1996).…”
Section: An Uncomfortable Topicmentioning
confidence: 99%
“…Previous research has shown either that there is little or no relationship between publication rate and marital and parental status of female faculty (Cole and Zuckerman 1987;Sonnert andHolton 1995a, 1996), or that, counterintuitively, single women publish less than married women faculty (Davis and Astin 1990). Also, male faculty, women faculty with children, and women faculty without children spend a comparable number of hours on their jobs (Winkler et al 1996). It is also difficult to explain the difference in publication rate by differences in how faculty allocate their time between different tasks or in their career motivation.…”
Section: Research Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…We use the survey responses to update a previous analysis of the salary and advancement of women faculty in atmospheric science (Winkler et al 1996;hereafter, WTS96). The earlier study investigated the large discrepancy in salary by gender for the "university/college" employment sector shown by the 1993 AMS membership survey (Zevin and Seitter 1994).…”
mentioning
confidence: 99%
“…After much discussion-and the sup- We use the survey responses to update a previous analysis of the salary and advancement of women faculty in atmospheric science (Winkler et al 1996;hereafter, WTS96). The earlier study investigated the large discrepancy in salary by gender for the "university/college" employment sector shown by the 1993 AMS membership survey (Zevin and Seitter 1994).…”
Section: Gary Gorskimentioning
confidence: 99%